2020
DOI: 10.1002/cam4.3226
|View full text |Cite
|
Sign up to set email alerts
|

Baseline total lesion glycolysis combined with interim positron emission tomography‐computed tomography is a robust predictor of outcome in patients with peripheral T‐cell lymphoma

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…SUVmax was not considered to have significant prognostic value in this study and similar results were also reflected by Xia et al [ 16 ] and Kitadate et al [ 17 ]. The exact prognostic value of pretreatment SUVmax for AITL remains controversial, though the study performed by Zhou et al showed that pretreatment SUVmax had independent prognostic value in PTCL [ 18 ].…”
Section: Discussionsupporting
confidence: 86%
“…SUVmax was not considered to have significant prognostic value in this study and similar results were also reflected by Xia et al [ 16 ] and Kitadate et al [ 17 ]. The exact prognostic value of pretreatment SUVmax for AITL remains controversial, though the study performed by Zhou et al showed that pretreatment SUVmax had independent prognostic value in PTCL [ 18 ].…”
Section: Discussionsupporting
confidence: 86%
“…Furthermore, new hypermetabolic lymphadenopathies and new hypermetabolic sites had developed since the first examination, in several different locations ( Figure 1 , right panel). Total lesion glycolysis (TLG) index was used to assess the changes in lymph node activities ( 6 ). As compared with the initial test, there was a marked 5.3-fold increase in whole-body TLG, with the increase in the post-booster test being twice higher in the right axillary region than in the left one.…”
Section: Case Reportmentioning
confidence: 99%
“…Early and accurate staging is extremely important in patients with PCL because treatment type and effectiveness varies greatly based on the stage of disease. Global disease assessments have been shown to provide prognostic information in several other cancers [41][42][43]. Creating objective standards for global disease assessment among institutions can help standardize patient care and augment collaborative efforts.…”
Section: Quantification Of Primary Cutaneous Lymphoma/ Disease Activi...mentioning
confidence: 99%